Utilizing chemically induced dimerization of FKBP to analyze endocytosis by live-cell imaging in budding yeast - Andrew K. Lamb; Santiago M. Di Pietro (STAR Protocols, 2022)
Summary: Chemically induced dimerization (CID) is a useful tool for artificially inducing protein-protein interactions. Although CID has been used extensively for live-cell microscopy applications in mammalian systems, it is rarely utilized in yeast cell biology studies. Here, we present a step-by-step protocol for the utilization of a CID system in live-cell microscopy experiments of budding yeast endocytosis. While focusing on the study of endocytosis, this protocol framework is adaptable to the study of other cellular processes in Saccharomyces cerevisiae.For complete details on the use and execution of this protocol, please refer to Lamb et al. (2021).